Status of vitamin D, paratharmone and serum calcium levels in perimenopausal women and their mutual correlation - Singh, Shashi; Sinha, Parul; Gupta, Uma; N. K., Gupta; Srivastava, Anand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The present study was carried out with an aim to assess Vitamin D, parathyroid hormone and calcium status in perimenopausal women and to find out their mutual correlation. Methods: The present work was carried out on in the Department of Obstetrics and Gynaecology, in collaboration with Department of Biochemistry at Era’s Lucknow Medical College and Hospitals, Lucknow, U.P. 80 healthy females aged 40-50 years were included in the study. Serum vitamin D, parathyroid hormone and calcium levels were assessed. Data was analyzed using ANOVA and Pearson correlation coefficient. Results: Osteopenia and osteoporosis was seen in 33 (41.3%) and 21 (26.3%) women respectively, 50 (62.5%) women had S. vitamin D levels <30 ng/ml, a total of 43 (53.8%) women had parathyroid hormone <75 pg/ml. No association between BMD status, parathyroid hormone, S. calcium levels and vitamin D levels was observed (p>0.05). Correlation between Vitamin D levels and Parathyroid hormone levels was weak and not significant. Conclusions: The findings of present study highlighted that perimenopausal phase should be regarded as a transition phase where a lot of physiological changes take place resulting in bone mineral density loss and fall in serum hormonal, vitamin and mineral levels. Owing to tremendous continuing changes the relationship between these parameters is vitiated and does not show a systematic change.